PENGARUH EARNING PER SHARE, RETURN ON ASSET DAN DEBT TO EQUITY RATIO TERHADAP HARGA SAHAM DENGAN KEBIJAKAN DIVIDEN SEBAGAI VARIABEL MODERASI - Tio Anggara; Nensi Yuniarti. Zs; Dinal Eka Pertiwi; Furqonti Ranidiah (Universitas Muhammadiyah Bengkulu, 2024)
This research was carried out using Moderated Regression Analysis (MRA) with the help of SPSS software version 22.0. The results of the Earning Per Share (EPS) research have no effect on share prices because the significance value of 0.221 is greater than 0.05. Return on Assets (ROA) has no effect because it has a significance value of 0.543 which is greater than 0.05. Debt To Equity Ratio (DER) has no effect on stock prices because the significance value of 0.306 is greater than 0.05. Furthermore, the dividend policy variable has an influence in moderating the Earning Per Share (EPS) variable on stock prices because the significance value of 0.008 is smaller than 0.05. The dividend policy moderation variable influences Return On Assets (ROA) on stock prices because the significance value is 0.006 more. smaller than 0.05. The dividend policy moderating variable has an influence in moderating the Debt To Equity Ratio (DER) variable on stock prices because the significance value of 0.011 is smaller than 0.05. Keywords: Earning Per Share, Return On Assets and Debt To Equity Ratio, Share Prices and Dividend Policy